2020
DOI: 10.3390/min10070588
|View full text |Cite
|
Sign up to set email alerts
|

Pyrite Textures, Trace Elements and Sulfur Isotope Chemistry of Bijaigarh Shales, Vindhyan Basin, India and Their Implications

Abstract: The Vindhyan Basin in central India preserves a thick (~5 km) sequence of sedimentary and lesser volcanic rocks that provide a valuable archive of a part of the Proterozoic (~1800–900 Ma) in India. Here, we present an analysis of key sedimentary pyrite textures and their trace element and sulfur isotope compositions in the Bijaigarh Shale (1210 ± 52 Ma) in the Vindhyan Supergroup, using reflected light microscopy, LA-ICP-MS and SHRIMP-SI, respectively. A variety of sedimentary pyrite textures (fine-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…A signature of bacterial reduction, framboidal pyrite (Figure 5b), is also compatible with seafloor processes. This feature has previously been reported in many sedimentary pyrites from several deep-sea sedimentary units (e.g., Mukherjee et al, 2020;Steadman et al, 2015) and massive sulfide ores rich in framboidal pyrite from Kuroko-type massive sulfide ore deposits in Japan (e.g., Ishizuka & Imai, 1998;Komuro & Sasaki, 1985). Thus, the sulfur of the seafloor basalt-hosted massive sulfide mineralization was derived from magmatic source and/or extracted from basaltic rocks with a small influence of bacterial activity in the seafloor environment.…”
Section: Source Of Sulfursupporting
confidence: 75%
See 1 more Smart Citation
“…A signature of bacterial reduction, framboidal pyrite (Figure 5b), is also compatible with seafloor processes. This feature has previously been reported in many sedimentary pyrites from several deep-sea sedimentary units (e.g., Mukherjee et al, 2020;Steadman et al, 2015) and massive sulfide ores rich in framboidal pyrite from Kuroko-type massive sulfide ore deposits in Japan (e.g., Ishizuka & Imai, 1998;Komuro & Sasaki, 1985). Thus, the sulfur of the seafloor basalt-hosted massive sulfide mineralization was derived from magmatic source and/or extracted from basaltic rocks with a small influence of bacterial activity in the seafloor environment.…”
Section: Source Of Sulfursupporting
confidence: 75%
“…As earlier studies suggested, sulfur is mostly liberated from sedimentary pyrite during prograde metamorphism when pyrite-pyrrhotite transformation occurs (e.g., Large et al, 2011;Pitcairn et al, 2010). High concentrations of trace elements such as As, Sb, Pb, and Cu of the hydrothermal pyrite are also similar to the composition of common sedimentary pyrite elsewhere (e.g., Mukherjee et al, 2020;Steadman & Large, 2016). Near-zero δ 34 S value of pyrite formed by the metamorphic rocks-hosted vein type mineralization could possibly be a result of mixing of sulfur between negative and strongly positive δ 34 S values during the remobilization of sulfur by metamorphic or hydrothermal processes (e.g., Hou et al, 2016).…”
Section: Source Of Sulfurmentioning
confidence: 76%
“…The fourth paper in the Special Issue explains sedimentary pyrite textures, their trace element and sulfur isotope ratios in pyrite varieties to understand paleo-redox conditions during the deposition of the Mesoproterozoic Bijaigarh Shale [4]. The combination of reflected light microscopy, LA-ICP-MS and SHRIMP-SI is involved in this study.…”
mentioning
confidence: 99%
“…However, the capabilities of the present-day LA-ICP-MS method in terms of high sensitivity and using mapping of trace elements continues to provide new insights into how these ore-forming processes take place, and in what order, during formation of gold [1], massive sulfide [2,3] and other deposits. This method yields plentiful trace element data on pyrite varieties in oil shales, which could be useful to develop inorganic-organic models of oil formation and predict the metal potential of adjacent pyrite mineralization [4]. Research on trace elements in pyrite of black shales in different basins should be considered as a new step useful for the recognition of sedimentation conditions and in the reconstruction of the geochemical evolution of oceans [5].…”
mentioning
confidence: 99%